2019
DOI: 10.1080/13691058.2019.1642517
|View full text |Cite
|
Sign up to set email alerts
|

Young adult US-born Latina women’s thoughts, feelings and beliefs about unintended pregnancy

Abstract: Current measures of unintended pregnancy underestimate the co-occurring, complex set of social, cultural, economic and structural factors that influence how women interpret unintended pregnancy. The purpose of this study was to prospectively explore young adult US-born Latinas' thoughts, feelings and beliefs about pregnancy, specifically unintended pregnancies and the sociocultural factors identified as contributors to those beliefs. In-depth interviews (n=20) were conducted with US born, English-speaking Lati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Research suggests that for many individuals, particularly people of color and people with low incomes, these socially normative expectations for pregnancy timing are perceived as unattainable; therefore, planning for pregnancy may be considered irrelevant 17 . For example, a study of US‐born Latina women reported that the notion of planning a pregnancy is unrealistic, as there is no ideal time to have a child 18 . Thus, evidence suggests the constructs of pregnancy planning and intendedness may be immaterial to the lived experiences of many.…”
Section: Critiques Of the Unintended Pregnancy Frameworkmentioning
confidence: 99%
“…Research suggests that for many individuals, particularly people of color and people with low incomes, these socially normative expectations for pregnancy timing are perceived as unattainable; therefore, planning for pregnancy may be considered irrelevant 17 . For example, a study of US‐born Latina women reported that the notion of planning a pregnancy is unrealistic, as there is no ideal time to have a child 18 . Thus, evidence suggests the constructs of pregnancy planning and intendedness may be immaterial to the lived experiences of many.…”
Section: Critiques Of the Unintended Pregnancy Frameworkmentioning
confidence: 99%
“… Coleman-Minahan and Samari (2020) found one component of a “good” father-daughter relationship was that fathers used their migration-related sacrifices to push their daughters to succeed in school, which in turn was associated with delayed sexual activity. And similar to Hernandez et al. (2020) , anticipated parental reactions to a pregnancy shaped several of our participants’ feelings about a hypothetical pregnancy.…”
Section: Discussionmentioning
confidence: 74%
“…These studies do not examine immigration policy or uncertainty, which is found within the social context in which events occur, not in the event itself ( Johnson‐Hanks, 2002 ). Even the limited studies on pregnancy intentions among Latinas rely on cultural norms or social disadvantage as explanatory variables, rather than immigration policy ( Aiken et al., 2015 ; Hernandez et al., 2020 ). Exploring reproductive aspirations allows us to describe how legal status and uncertainty constrain people's hopes and dreams, which are essential to reproductive justice and self-determination.…”
Section: Introductionmentioning
confidence: 99%
“…Research in this area may also benefit from examining cultural and societal expectations for reproduction, as these may also shape experiences with reproductive coercion. Sociocultural variables, such as beliefs about contraception and unintended pregnancy, may worsen adverse health outcomes related to reproductive coercion and ultimately limit the reproductive autonomy of people who can become pregnant (Hernandez et al, 2020). Research that addresses social and cultural norms surrounding reproductive coercion is needed in order to fully understand racial/ethnic disparities that have been documented by this study and others.…”
Section: Discussionmentioning
confidence: 99%